Análisis de la influencia del fenómeno stick-slip en los esfuerzos de los cortadores de una broca PDC, mediante simulación por elementos finitos (2015)
This article presents a methodology for measuring the mechanical stresses present as a result of torsional vibration phenomena. Additionally, a qualitative analysis of the behavior of drilling tools under conditions of stick-slip is presented. Finally. The stress overload as a result of Stick-Slip is evidenced and approximate values for the operating parameters for drilling without significant damage in drilling tools are presented.